Evaluation of laparoscopic retroperitoneal approach for management of various renal calculi - ., Rudramani; Singh, Vikas; Kumar, Shesh; Kumar, Anil; Kumar, Shailendra; Singh, Manish Kr. (International Surgery Journal, 2018)
Background: Despite the availability of Multimodality treatment for management of renal calculi as ESWL (Extra Corporeal Shock Wave Lithotripsy), PCNL (Percutaneous nephrolithotomy), URS (Ureterorenoscopy), RIRS (Retrograde intrarenal surgery) and open surgery and Percutaneous nephrolithotomy (PCNL), the gold standard, laparoscopic pyelolithotomy is an alternative treatment modality as long as the operator has adequate laparoscopic experience. Evaluation of Laparoscopic retroperitoneal approach for management of various renal calculi must be done to get the efficacy of the procedure according to the calculus and renal morphology. Methods: Laparoscopic retroperitoneal pyelolithotomy/nephrolithotomy was performed on 58 patients with various renal calculi patterns viz. solitary pelvic calculus, staghorn calculus, staghorn calculus with calyceal and isolated calyceal calculi. Extended pyelolithotomy, Gilvernet’s technique were used as per the need. Results: Out of the 58 cases with renal calculi, solitary renal pelvic stones (n=23; 39.7%) were most common followed by staghorn (n=11; 19% Mean size 4.40±1.17 cm) and isolated caliceal stones (n=9; 15.5% with Mean size2.21±0.25 cm) respectively. There were 15 (25.9%) cases with mixed stones (11 cases solitary renal pelvic and isolated caliceal stones and 4 cases had staghorn and isolated caliceal stones). Stone clearance was 93.3 to 100%. Conclusions: laparoscopic retroperitoneal approach is a useful modality for clearance of renal calculi of different types with minimum complications and a high success rate. However, the technique seems to have a limited role for isolated caliceal stones where direct or C-arm guided nephrolithotomy can be performed for better clearance of stones.